2011
DOI: 10.1136/postgradmedj-2011-130298
|View full text |Cite
|
Sign up to set email alerts
|

Association of cardiac and non-cardiac chronic disease comorbidity on glycaemic control in a multi-ethnic population with type 1 and type 2 diabetes

Abstract: The prevalence of CDCM is higher in SAs compared to WEs with type 2 diabetes, whereas the prevalence of NCCM is higher in WEs compared to SAs. Taking into account comorbidities, SAs (compared to WEs) with type 2 diabetes had an excess risk of having HbA1c ≥7% ranging from 1.86- to 2.27-fold. Further research is needed to identify the reasons for unfavourable metabolic conditions in SAs and also develop and evaluate interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 39 publications
(21 reference statements)
1
37
0
Order By: Relevance
“…One of these was longitudinal but had a very small South Asian sample size of 86 patients [38]. The other three were cross sectional [16,28,32] and two of these reported pooled data on South Asians rather than the individual ethnicities groups [28,32]. Pakistanis and Indians are not reported to vary largely in their genetic makeup and so the differences in cardiovascular risk reported here likely reflect other factors.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…One of these was longitudinal but had a very small South Asian sample size of 86 patients [38]. The other three were cross sectional [16,28,32] and two of these reported pooled data on South Asians rather than the individual ethnicities groups [28,32]. Pakistanis and Indians are not reported to vary largely in their genetic makeup and so the differences in cardiovascular risk reported here likely reflect other factors.…”
Section: Discussionmentioning
confidence: 98%
“…Differences in diabetes incidence rates [8,12,25] and CVD rates [8,24,26] have been evaluated in many studies. Ethnic differences in age of diabetes diagnosis [11,12,27], diabetes prevalence [8,19], HbA 1c levels [28,29], body composition [8,9,30], smoking [28,31], physical activity [12,32,33] and diet [6,34] have all been reported previously. Many studies have also reported effects of SES on diabetes [35,36] and CVD incidence [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may reflect the increased rates of abdominal obesity in SA compared to Europids. [23][24][25] Furthermore at any given body mass index (BMI), SA migrants were found to have 3.9% (p<0.001) greater body fat compared to Europids. 26 The largest case-control study to examine the earlier age of MI in SA found that the age gap in first presentation of MI versus other groups was largely explained by higher rates of conventional risk factors.…”
Section: Ii) Etiologymentioning
confidence: 97%
“…However, this treatment may be helpful for chronic tendinopathies resistant to typical treatments. 3 In our case, the patient developed an exuberant local inflammatory reaction 1 week after injection with PRP. 1 Only 1 case report described the development of dense exuberant synovitis of the subacromial space after acromioplasty and postoperative PRP injection in a 66-year-old man.…”
Section: Case Reportmentioning
confidence: 56%